Mail Filing Application At Akper Rumkit TK. III Manado - Deyidi Mokoginta (Jurnal Indonesia Sosial Teknologi, 2023)
In today's technological era, the important role of technology in supporting administrative activities in various agencies, including government and private institutions, cannot be ignored. One of the critical aspects of administration is document management, especially when it comes to archiving incoming and outgoing mail. Traditional document archiving by storing physical documents faces obstacles in large storage requirements, long search times, and the risk of damage due to attacks by intruding animals. This research focuses on developing a Mail Archiving System Application with a computerized approach at the Akper Rumkit Tk.III Manado Campus. The research method involves direct observation in the field, with the research object being administrative administration. The data collection process is done by searching for information from various sources, including books, journals, the internet, and interaction with the administrative administration. The results of this study created a computerized incoming and outgoing mail filing application. The application is designed to manage mail data efficiently and effectively, minimizing the constraints that often arise in traditional archiving. With this application, the mail filing process is expected to be more optimal, speed up the search for documents, and reduce the risk of damage that may arise. As an innovative solution, implementing this application is expected to positively contribute to improving administrative performance at the Akper Rumkit Tk.III Manado Campus.